Analysis Semiotics of Subaltern in the "Mulan" Film: Analisis semiotika subaltern dalam film Mulan karya Niki Caro - Dini Zaradika (Jurnal Masyarakat Maritim, 2021)
Niki Caros original film is a Disney remake of the same name. The film tells the story of a tough woman who replaces her father as a war soldier in China and manages to win the Chinese empire back. The film also raises the issue of the position of women in Chinese society which is still thick with pariarchal culture.This research used a qualitative research with Roland Barthes semiotic analysis. The purpose of this study was to analyze the subaltern that occurred to Chinese women in Mulan's film. The results of this study explain the impossibility of women getting the same place as men even though they have struggled together as a soldier. Women will always be subalterns, especially in a society steeped in patriarchal culture.